The never game [large type] - Deaver, Jeffery (Deaver, Jeffrey. Colter Shaw, 2019)
"From the bestselling and award-winning master of suspense, the first novel in a thrilling new series, introducing Colter Shaw. "You have been abandoned." A young woman has gone missing in Silicon Valley and her father has hired Colter Shaw to find her. The son of a survivalist family, Shaw is an expert tracker. Now he makes a living as a "reward seeker," traveling the country to help police solve crimes and private citizens locate missing persons. But what seems a simple investigation quickly thrusts him into the dark heart of America's tech hub and the cutthroat billion-dollar video-gaming industry. "Escape if you can." When another victim is kidnapped, the clues point to one video game with a troubled past--The Whispering Man. In that game, the player has to survive after being abandoned in an inhospitable setting with five random objects. Is a madman bringing the game to life? "Or die with dignity." Shaw finds himself caught in a cat-and-mouse game, risking his own life to save the victims even as he pursues the kidnapper across both Silicon Valley and the dark 'net. Encountering eccentric game designers, trigger-happy gamers and ruthless tech titans, he soon learns that he isn't the only one on the hunt: someone is on his trail and closing fast"--